2020
DOI: 10.1002/humu.24069
|View full text |Cite
|
Sign up to set email alerts
|

General population ZBTB18 missense variants influence DNA binding and transcriptional regulation

Abstract: Genetic variation of the multi‐zinc finger BTB domain transcription factor ZBTB18 can cause a spectrum of human neurodevelopmental disorders, but the underlying mechanisms are not well understood. Recently, we reported that pathogenic, de novo ZBTB18 missense mutations alter its DNA‐binding specificity and gene regulatory functions, leading to human neurodevelopmental disease. However, the functional impact of the general population ZBTB18 missense variants is unknown. Here, we investigated such variants docum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 44 publications
(100 reference statements)
0
24
0
Order By: Relevance
“…Thirdly, our molecular modelling studies reveal that His441 is critical as a zinc-coordinating reside in the second zincnger motif. As all four zinc ngers are essential for ZBTB18 to bind DNA [31,55], a His441Gln mutation could destabilize the protein, disrupt sequence-speci c binding, alter transcriptional regulation in cells, or all of the above. Indeed, recent studies of a p.Asn461Ser mutation detected in a child with ID [46] demonstrated that such a variant not only resulted in reduced steady-state levels of the mutant protein, but also compromised sequence-speci c DNA binding and transcriptional repression [31].…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, our molecular modelling studies reveal that His441 is critical as a zinc-coordinating reside in the second zincnger motif. As all four zinc ngers are essential for ZBTB18 to bind DNA [31,55], a His441Gln mutation could destabilize the protein, disrupt sequence-speci c binding, alter transcriptional regulation in cells, or all of the above. Indeed, recent studies of a p.Asn461Ser mutation detected in a child with ID [46] demonstrated that such a variant not only resulted in reduced steady-state levels of the mutant protein, but also compromised sequence-speci c DNA binding and transcriptional repression [31].…”
Section: Discussionmentioning
confidence: 99%
“…More broadly, it is tempting to speculate that general population missense variants within conserved domains function as modifier alleles to influence TF signalling within cells. Nevertheless, it is relevant to consider that the weak yet measurable functional impact of general population missense ZBTB18 variants stands in stark contrast to disease-associated variants, the latter of which are endowed with strong effects on transcriptional regulation (Hemming et al, 2020).…”
Section: Exploring the Impact Of Missense Variation On Transcription ...mentioning
confidence: 99%
“…luciferase reporter assays, chromatin immunoprecipitation (ChIP), electrophoretic mobility shift assays (EMSAs), in utero electroporation (IUE) studies; as well as as well as more recently reported screening methods (e.g. multi-plex reporter assays (MPRAs) (Mulvey, Lagunas, & Dougherty, 2021), mammalian targeted damID (MaTaDa) (Cheetham et al, 2018), Cut&Run (Meers, Bryson, Henikoff, & Henikoff, 2019)) and, where feasible, binding free energy calculations (Blake et al, 2021;Hemming et al, 2019;Hemming et al, 2020)) in order to study the DNA-binding, protein-protein interaction and transcriptional regulatory signalling properties of TFs as well as their query variants ( N/A Note: The severity of functional missense variants are defined by their impact on TF proteins to signal via co-operation, competition as well as combination. Category 0 variants show negligible functional impact, based upon these three mechanistic criteria.…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%
See 2 more Smart Citations